Factors affecting foreign direct investment decision in Malaysia / Farah Hannah Mohamad Idris - Mohamad Idris, Farah Hannah (Faculty of Business and Management, 2018)
Foreign Direct Investment (FDI) show a crucial role in bring on the development and economic advancement of a country. In addition, cultivate countries look massively on FDI to advance their economy as they aspect capital shortage for their development process. In capitals and technology FDI not only lead, but also skills toward developing countries. Ended up helping the countries to develop faster by pleasing the country's needs. The heavy growth performances experienced by Malaysia economy largely depends on the FDI. FDI make economic growth by developing capital arrangement through the promotion of export growth, inflation of production capacity, and creation of employment in Malaysia. FDI inflows of Malaysia initiated fluctuating from 1996 to 2010 and this high volatility of Malaysia FDI inflows bring the researchers' attention to study the factors that affecting FDI decision in Malaysia by using the annual data from year 1987-2016. Multiple linear regressions model is enforced to study the relationship between explanatory variables (growth domestic product, inflation rate, exchange rate, and trade openness) and explained variable (Malaysia FDI). Empirical results show that growth domestic product, and inflation rate significantly and positively affect Malaysia FDI decision. In other hands, exchange rates also significantly affect Malaysia FDI decision; when Ringgit Malaysia depreciates against other currencies, FDI decision of Malaysia decrease. Last but not least, trade openness lagged to establish a significant relationship with Malaysia FDI decision.